1996
DOI: 10.1148/radiology.201.3.8939214
|View full text |Cite
|
Sign up to set email alerts
|

Elapsed radiation therapy treatment time as a predictor of survival in patients with advanced head and neck cancer who receive chemotherapy and radiation therapy.

Abstract: The time between radiation therapy treatments is strongly predictive of survival in patients undergoing sequential chemotherapy and radiation therapy. The use of induction chemotherapy does not negate the need to avoid treatment interruptions during definitive radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…reports of practical oncology and radiotherapy x x x ( 2 0 1 5 ) xxx-xxx reports of practical oncology and radiotherapy x x x ( 2 0 1 5 ) xxx-xxx 5 LRC a : Try to maintain OTT k < 45-50 days [35,41]. In any case, avoid OTT k ≥60 days (LRC a and/or OS d ) [37,43] Delays ≥5 days must be avoided (LRC a and/or OS d ) [44,46,52] No prognostic significance: No. of consecutive treatment days missed [43] and gap position [44,52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reports of practical oncology and radiotherapy x x x ( 2 0 1 5 ) xxx-xxx reports of practical oncology and radiotherapy x x x ( 2 0 1 5 ) xxx-xxx 5 LRC a : Try to maintain OTT k < 45-50 days [35,41]. In any case, avoid OTT k ≥60 days (LRC a and/or OS d ) [37,43] Delays ≥5 days must be avoided (LRC a and/or OS d ) [44,46,52] No prognostic significance: No. of consecutive treatment days missed [43] and gap position [44,52].…”
Section: Resultsmentioning
confidence: 99%
“…In adjuvant radiotherapy, may be significant early gaps in R0 l and late gaps in R1 m pts and total n • of gaps in both [52]. No adverse effect if break in the first 3 weeks [54] TCP n significantly correlated with OTT k and gap duration [49] Impossible to establish if weekends scored as gaps is important [49] Induction chemo not negate to avoid interruptions [46] OTT k protraction significantly affected LRC a only in G1-2 tumors [47], especially in laryngeal subgroup [50] (*) ↓ 12% preservation of voice in laryngeal cancer [50] Larynx…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect evidence of the negative consequences of unplanned radiation treatment breaks comes from several studies of total radiation treatment time. Unintended prolongation of the total time of definitive radiotherapy is associated with worse locoregional control [14 -16, 18] and survival [12,17]. In the case of postoperative treatment of head and neck cancer, there can be significant delays in the "package time"-the time from surgery to completion of postoperative radiotherapy.…”
Section: Clinical Consequences Of Radiation Treatment Breaksmentioning
confidence: 99%
“…They concluded that adherence appeared to be related to improved overall survival and an increase in average survival time. Alden et al (1996) stressed the importance of avoiding treatment lapses for head and neck cancer patients receiving radiation therapy. They concluded that time between radiation treatments is ''strongly predictive of survival in patients undergoing sequential chemotherapy and radiation therapy'' (Alden et al,p.…”
Section: Common Treatment Optionsmentioning
confidence: 99%